Repairing the State: Policy Repair in the Frontline Bureaucracy. - Masood, Ayesha; Nisar, Muhammad Azfar (Public Administration Review, 2022)
Research on street‐level bureaucrats has identified their role as policy entrepreneurs through the adoption and advocacy of policy innovations. This article adds to this research by underscoring how street‐level bureaucrats use creativity and improvisation to find contextual solutions for emergent local policy problems in response to scarcity. We suggest that these practices of policy repair allow frontline bureaucracies to deal with personnel, process, and material scarcity and maintain public service delivery even in resource‐scarce environments. Using ethnographic data from Punjab, Pakistan, we show that this repair work is collaborative, client‐centered, and motivated by compassion and kindness. Our research indicates that emergent and improvised policy repair allows frontline bureaucracies to be resilient and responsive to scarcity and changing service demands. Our findings further suggest that inclusion of street‐level bureaucrats in formal policy decisions can help develop context‐specific solutions to emergent problems of public service delivery. Evidence for Practice: Street‐level bureaucrats (SLBs) face multiple types of scarcity during policy implementation—material scarcity, where they do not have enough equipment or space for their work; process scarcity, where officially sanctioned menu of routines or procedures do not account for local situations; and personnel scarcity, where they do not have enough workforce or expertise for their tasks.SLBs do policy repair—use creativity and innovation in their day‐to‐day work to find local and contextualized solutions for their localized service limitations, to overcome scarcity, and to deal with the vulnerability of bureaucratic systems.Allowing SLBs to use creativity and improvisation for local and emergent problems can create more robust and resilient public service delivery systems.Repair requires implicit and local knowledge of bureaucratic systems; inclusion of SLBs in formal policy decisions is necessary to develop context‐specific solutions to emergent problems of public service delivery.